Research Creativity - Haider A. Naqvi (ziauddin University, 2024)
It is common place to assess research productivity through citation index, impact factor or the number of publications. These are contentious parameters to quantify research creativity. Individuals are generally aware of the impact of their research in the domain of policy and practice. However, the various avenues of research dissemination and marketing of products have made the matters complicated. As one advances through his professional research-career one moves on to robust methodology (including research design) based on the research question and epidemiological acumen.....